Radio Protective Effects of Ginseng Extract in Gamma-Rays Induced Chromosomal Damages of Human Lymphocyte - M. Syaifudin; Jie- Young Song; Yun- Sil Lee; Chang- Mo Kang (Atom Indonesia, 2008)
Ginsan, a polysaccharide extracted from Panax ginseng and subsequently referred as ginseng, posses various biological properties as an anticancer and antioxidant agent. Ginseng also approved effective against radiation effects through its immunomodulating actions in whole body irradiated mouse. But its protective effects on radiation induced DNA damage are not thoroughly investigated, mainly in human. This experiment aimed to assess the effects of ginseng at 2 working doses in suppressing radiation effects of human peripheral blood lymphocyte (PBL) i.e. chromosome aberration and micronuclei yields. The treatment times were 24 hours before, subsequently (0 hour) or 3 hours after and irradiation with gamma rays at doses of 0.5 - 2.0 Gy (dose rate of 3.16 Gy/min). Treated and untreated blood cultivation and metaphase spreading technique was done according to standard procedures. Results showed that without ginseng treatments, radiation significantly increased dicentrics and micronuclei frequencies. Different with the results in mouse study, however, our results indicated that none of the experimental concentrations of ginseng crude water extract tested had an effect on baseline chromosomal aberration and micronuclei (MN) yields in PBL. A protective effect was only seen in chromosome aberration yields of sample irradiated with 2.0 Gy and treated with ginseng 3 h post irradiation rather than 24 h pre-irradiation in one volunteer. Opposite results that ginseng suspected to be a weak radiosensitizer was found in some cases. This may be due to discrepancies exist in route of treatment and its fundamental mechanisms of protective action between both studies. Even though in general it was not effective, the possible mechanism involved in radioprotective influence of ginseng is discussed.